Evaluation of dynamic strain aging behaviour of additively manufactured inconel 718 - Sriram, T. (Nanyang Technological University, 2024)
Additively Manufactured (AM) Inconel 718 (IN718) has gained significant attention for its potential applications in high-temperature environments due to its outstanding mechanical properties and corrosion resistance. However, understanding the behaviour of AM IN718 under dynamic loading conditions, particularly regarding Dynamic Strain Aging (DSA), remains essential for ensuring its performance and reliability. This report presents an experimental investigation of the DSA behaviour of AM IN718 under compression. High temperature compression tests are conducted, and analyses of the data are performed to examine the Portevin–Le Chatelier (PLC) effect in AM IN718. Features of PLC instabilities are studied at temperatures of 400°C, 500°C, 550°C, 600°C and 650°C, and at strain rates between 10-1 and 10-4 s-1 on cylindrical AM IN718 samples of different Aspect Ratios (ARs) and machining directions in As-Printed (AP) conditions. Serrations of Type C and an average serration amplitude of 0.1-0.2kN are predominant across the range of temperatures and strain rates explored. PLC amplitude generally increases with decreasing strain rate with all ARs. Also, PLC serrations start at a higher strain point with increasing temperature and decreasing strain rate. Similarly, a combination of low temperature and high strain rate results in no formation of serrations. These findings contribute to enhancing our understanding of DSA in AM IN718 and provide insights to optimise the material for high performance applications in dynamic and high temperature environments.